Energy Metabolism Characterization of a Novel Cancer Stem Cell‐Like Line 3AB‐OS. Issue 2 (February 2014) - Palorini, Roberta; Votta, Giuseppina; Balestrieri, Chiara; Monestiroli, Andrea; Olivieri, Sandro; Vento, Renza; Chiaradonna, Ferdinando
ABSTRACT Cancer stem cells (CSC) have a central role in driving tumor growth. Since metabolism is becoming an important diagnostic and therapeutic target, characterization of CSC line energetic properties is an emerging need. Embryonic and adult stem cells, compared to differentiated cells, exhibit a reduced mitochondrial activity and a stronger dependence on aerobic glycolysis. Here, we aimed to comparatively analyze bioenergetics features of the human osteosarcoma 3AB‐OS CSC‐like line, and the parental osteosarcoma MG63 cells, from which 3AB‐OS cells have been previously selected. Our results suggest that 3AB‐OS cells depend on glycolytic metabolism more strongly than MG63 cells. Indeed, growth in glucose shortage or in presence of galactose or pyruvate (mitochondrial specific substrates) leads to a significant reduction of their proliferation compared to MG63 cells. Accordingly, 3AB‐OS cells show an increased expression of lactate dehydrogenase A (LDHA) and a larger accumulation of lactate in the culture medium. In line with these findings 3AB‐OS cells as compared to MG63 cells present a reduced mitochondrial respiration, a stronger sensitivity to glucose depletion or glycolysis inhibition and a lessened sensitivity to oxidative phosphorylation inhibitors. Additionally, in contrast to MG63 cells, 3AB‐OS display fragmented mitochondria, which become networked as they grow in glucose‐rich medium, while almost entirely loose these structures growing in low glucose. Overall, our findings suggest that 3AB‐OS CSC energy metabolism is more similar to normal stem cells and to cancer cells characterized by a glycolytic anaerobic metabolism. J. Cell. Biochem. 115: 368–379, 2014. © 2013 Wiley Periodicals, Inc.